UVA Induced Oxidative Stress Was Inhibited by Paeoniflorin/Nrf2 Signaling or PLIN2 - Lu, Yan-Song; Jiang, Yuan; Yuan, Jin-ping; Jiang, Shi-Bin; Yang, Yang; Zhu, Pei-yao; Sun, Yu-zhe; Qi, Rui-qun; Liu, Tao; Wang, He-Xiao; Wu, Yan; Gao, Xing-Hua; et al. (Frontiers in Pharmacology, 2020)
Photodamages caused by UVA radiation induced oxidative injuries are closely related to photoaging and skin cancer. Paeoniflorin (PF), extracted from the root of Paeonia lactiflora, has been reported to be an effective antioxidant. PLIN2, known as adipose differentiation-related protein, has been previously to be involved in the regulation of oxidative stress. In this study, we detected the protective property of PF against UVA radiation and the function of PLIN2 in vivo and in vitro. We found that PF pre-treatment could prominently alleviate the cytotoxicity of UVA radiation in human fibroblasts, and mice pre-treated with PF were likely to be protected from UVA radiation. We also confirmed that PF pre-treatment could reduce the generations of ROS and MDA, and increase the activity of SOD after UVA radiation. Western blot and immunohistochemical analysis revealed that in response to either UVA exposure or PF treatment, Nrf2 and its target genes HO-1 and NQ-O1 were significantly increased. In absence of Nrf2, PF treatment lost the cytoprotective property against UVA radiation in fibroblasts. In addition, we have found that UVA induced oxidative stress led to upregulation of PLIN2 which could be decreased again by PF, and overexpressed PLIN2 promoted cell proliferation and reduced the generation of MDA. We have also found a compensatory protection of PF and PLIN2 in cell prevention from UVA induced oxidative stress. Furthermore, PLIN2 overexpression and the combination of PF pre-treatment corporately inhibit UVA induced oxidative stress. In conclusion, our study demonstrated that UVA induced cytotoxicity was inhibited by PF/Nrf2/HO-1/NQ-O1 signaling pathway or PLIN2, and combining PF and PLIN2 overexpression demonstrated additive effect against UVA related oxidative stress.